Supporting people with post‐stroke aphasia to live well: A cross‐sectional survey of Speech & Language Therapists in Ireland. (27th May 2020) - Manning, Molly; Cuskelly, Ciara; Russ, Erin; Franklin, Sue
Abstract: Living well with post‐stroke aphasia is supported by responsive, collaborative heath and related services, aphasia information and training for people with aphasia (PWA) and their social networks, and opportunities to contribute and participate autonomously in their communities. Several international surveys indicate shortcomings in the provision of long‐term support and, in Ireland, while there is a lack of data around service provision for PWA, there is evidence that post‐acute stroke services are fragmented and under‐resourced. The aim of this study was to survey Speech & Language Therapists (SLTs), due to their unique role in aphasia management, to understand what SLT and related support services and aphasia information and training are currently available to support living well with aphasia in Ireland. We developed and piloted a self‐administered, web‐based cross‐sectional survey with questions informed by a systematic review and qualitative evidence synthesis around living well with aphasia, and with input from a Public and Patient Involvement aphasia advisory group. Data from 95 SLTs working with PWA were analysed using descriptive statistics. Although SLT was generally available for PWA, the results highlight access barriers and evidence‐practice gaps in terms of the amount, intensity and timing of SLT to be maximally effective and there was a lack of PWA input into service design and evaluation. Access to other relevant supports such as mental health services was inconsistent and there was a lack of community support for families. There were shortcomings in access to aphasia information/training for PWA, families, friends and other healthcare professionals. There is a need for a coordinated and standardised approach to supporting PWA across Ireland. This study addresses an evidence gap around the provision of stroke services for PWA and is part of a larger project aiming to produce recommendations for improving person‐centred support to facilitate living well with aphasia.